Size-dependent nonlinear absorption and refraction of Ag nanoparticles excited by femtosecond lasers - 范光华 曲士良 郭忠义 王强 李中国 (Chinese physics B, 2012)
Silver （Ag） nanoparticles with different average sizes are prepared, and the nonlinear absorption and refraction of these nanoparticles are investigated with femtosecond laser pulses at 800 nm. The smallest Ag nanoparticles show insignificant nonlinear absorption, whereas the larger ones show saturable absorption. By considering the previously reported positive nonlinear absorption of 9 nm Ag nanopartieles, the nonlinear absorptions of Ag nanopartieles are found to be size-dependeut. All these nonlinear absorptions can be compatibly explained from the viewpoints of electronic transitions, energy bands and electronic structures in the conduction band of Ag nanoparticles. The nonlinear refraction is attributed to the effect of hot electrons arising from the intraband transition in the s p conduction band of Ag nanoparticles.